Language learners' engagement in hybrid classroom settings: A systematic review - Nurharjanto, Asfar Arif (LingTera, 2023)
Students' engagement has been seen as a crucial part of learning as it determines their success in getting the most out of the learning process. The present study aims to identify the trends and to evaluate the main findings of a number of articles on students' engagement concerning the hybrid classroom settings. This study started with employing some keywords to select articles from several databases to review. A systematic review following the PRISMA framework was employed as the research method. The articles were then analyzed by means of content analysis. The findings suggest that most articles involved university students as the main participants, with the sample size ranging from 100 to 500 students. In terms of methods, most studies used quantitative measures by employing surveys in comparison with the less observed qualitative or mixed methods. The findings show that the selected articles focused on improving students' engagement, developing tools for measuring engagement, and determining factors affecting engagement in relation to technology. Further suggestions regarding the implications and future research are discussed.